Pellagra in a patient with primary Sjögren's syndrome. (18th June 2014) - Ben Ghorbel, Imed; Litaiem, Noureddine; Chelly, Ines; Houman, Habib
Abstract : A 27-year-old woman presented with persistent dryness of the mouth and eyes. She presented with permanent photodistributed rash involving the face and distal extremities. Laboratory tests showed positive Sjögren's syndrome (SS)-A and SS-B antibodies. Histological examination of minor salivary gland biopsy revealed inflammatory infiltration grade 4 according to Chisholm's classification. Skin biopsy showed acanthosis, hyperkeratosis in the epidermis and little inflammatory infiltrate in the dermis. There was an infiltration of CD4 T lymphocytes in the dermis. Based on the characteristics of the dermatitis and on a rapid response to niacin replacement, the diagnosis of pellagra was carried out. A complete resolution of the dermatological signs was obtained within 2 months. To the best of our knowledge, the association between primary SS and pellagra has never been reported. We emphasise the possible mechanisms of this association.